Kajian Sosial Ekonomi Pelaku Usaha Pada Objek Wisata Bukit Kasih Kanonang Kabupaten Minahasa - Tuwo, Olivia; Kaihatu, Jolanda Esther; Poli, Ellen Eva (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2024)
The sub-focus of this research is on the conditions of visits to tourist sites, the socio-economic conditions of business actors, and the educational background of business actors. This research seeks to determine the socio-economic conditions of business actors in the Bukit Kasih area. Kanonang tourism is an object. This study uses a qualitative descriptive methodology with observation, interviews, and documentation as data collection tools. These findings show how labor affects the income of Bukit Kasih business actors, which fell during the COVID-19 pandemic. The size of the income earned by Bukit Kasih entrepreneurs is influenced by the company's capital. The income of Bukit Kasih business actors has dropped significantly since the outbreak of the pandemic in early 2019. Business actors generally lack business management skills.